Using Pegylated Graphene Oxide to Achieve High Performance Solid Polymer Electrolyte Based on Poly - Eslami, Behnam; Ghasemi, Ismaeil; Esfandeh, Masoud (Polymers, 2023)
Solid polymer electrolytes (SPEs) have emerged as a promising avenue for developing flexible lithium-ion batteries. However, the low ionic conductivity of polymers remains a primary challenge that has been the subject of intensive research efforts in recent years. In this work, polyethylene oxide (PEO), polyvinyl alcohol, lithium perchlorate (LiClO[sub.4]), and graphene functionalized with polyethylene glycol (FGO) have been used to prepare SPE/FGO electrolytes by casting solution technique. X-ray diffraction (XRD) and differential scanning calorimetry (DSC) confirmed the reduction of SPE crystals and the increase of amorphous phases. The results demonstrated that the presence of functionalized graphene had an effective role in reducing crystallinity. Furthermore, the thermal and mechanical stability of the samples were corroborated through thermogravimetric analysis (TGA) and tensile tests, respectively. Notably, the samples exhibited adequate ionic conductivity at room temperature, with the highest ionic conductivity of 5.2 × 10[sup.−5] S·cm[sup.−1] observed for 2%wt of FGO in SPE (SPE/FGO(2)).